LINGUISTIC INDIVIDUALITY OF HRYHORIY BILOUSAS ONE OF HRYHORIY SCOVORODA’S IMAGE CREATORS - Marchuk, Lyudmyla (Verbum, 2015)
Ukrainian linguists pay great attention to studying individual styles of artistic word masters. This theme is analysed in many scientific works by S. Bybyk, I. Bilodid, V. Vashchenko, S. Yermolenko, V. Kalashnyk, T. Kosmeda, A. Moysiyenko, M. Pylypynskiy, O. Potebnia, V. Rusanivskiy, N. Solohub, L. Stavytska, V. Stateyeva, H. Siuta, V. Chabanenko, etc. In this aspect, the famous writer Hryhoriy Bilous played a great role in forming artistic, publicistic, epistolary styles of the modern Ukrainian literary language. We are acquainted with his poems, dramatic poems, the novel “Rudoman”, collection of letters “Slova, slova, spasite nashi dushi…”. In mosaic diversity of letters, the main plotline is vivid: day-to-day movement of a person from the first realization of the sojourning in this world to the secret of the word, to its unknown depth. Besides the letters, Hryhoriy Bilous is also known as a glorifier of Hryhoriy Scovoroda, where the symbol of his artistic works is presented. Hryhoriy Bilous is a writer of wide artistic range. His verses, poems and researches are dedicated to fighters for the truth of the XIX–XXth centuries, they assert the inheritance of the spiritual potential of Ukrainian people’s prophets. The author puts figures of Hryhoriy Scovoroda, Taras Shevchenko, and Vasyl Stus into continuous line of successive awakeners of national spirit, he illustrates their incontestable influence on the forming of national consciousness and active civic position, and that is very important for modern Ukrainian young people. The author teaches the exactingness to the Word, to systematic work on it, associative thinking, abilities to generalize, and responsibility for everything written and said. Above all, with the help of his works, he reminds us about historically and spiritually important people in the history of Ukraine, sets an example by his own publicistic and epistolary styles; the author works in the genre of poetic drama and his works have become a source of awakening of self-consciousness and national pride of Ukrainian people.
Keywords: individual style; artistic; journalistic; epistolary style; associative thinking